2007
DOI: 10.1093/ndt/gfm638
|View full text |Cite
|
Sign up to set email alerts
|

Urinary interleukin-18 is an acute kidney injury biomarker in critically ill children

Abstract: Urinary IL-18 rises prior to SCr in non-septic critically ill children, predicts severity of AKI and is an independent predictor of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
120
2
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(143 citation statements)
references
References 22 publications
10
120
2
9
Order By: Relevance
“…From this study it was found that IL-18 seems to be a very reliable and accurate marker of subclinical nephropathy, especially tubulopathy in HIV-infected patients on TDF. This finding agrees with other workers that IL-18 might be used as a marker to identify patients with proximal tubular dysfunction [11,12]. Finally, the present findings further suggest that longer periods of observation may increase the number of patients with subclinical signs of nephropathy in patients exposed to TDF regimen since proximal tubular dysfunction in these patients is progressive.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…From this study it was found that IL-18 seems to be a very reliable and accurate marker of subclinical nephropathy, especially tubulopathy in HIV-infected patients on TDF. This finding agrees with other workers that IL-18 might be used as a marker to identify patients with proximal tubular dysfunction [11,12]. Finally, the present findings further suggest that longer periods of observation may increase the number of patients with subclinical signs of nephropathy in patients exposed to TDF regimen since proximal tubular dysfunction in these patients is progressive.…”
Section: Resultssupporting
confidence: 93%
“…The difference between the groups was highly statistically significant at different time point studied. Perhaps, this finding is expected since IL-18 increases in urine only under condition of a marked tubular damage, apoptotic tubular cell shedding, and cell necrosis, associated with deterioration of renal function [11]. From this study it was found that IL-18 seems to be a very reliable and accurate marker of subclinical nephropathy, especially tubulopathy in HIV-infected patients on TDF.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…However, in noncardiac PICU patients, performance of these same biomarkers is variable, with area under the curve receiver-operating characteristic (AUC-ROC) values ranging from 0.54 to 0.85 (Table 1) (4-7). Our previous data indicate that children suffering AKI.48 hours after admission are at highest risk for poor clinical outcome, including prolonged length of stay, need for RRT, or mortality (5,8). Thus, identification of patients at risk of AKI early in their intensive care unit (ICU) admission may help clinicians optimize the timing of resuscitative and supportive therapies.…”
Section: Introductionmentioning
confidence: 99%